Dysphagia from a neurogeriatric point of view: Pathogenesis, diagnosis and management - Warnecke, Tobias; Bauer, Jürgen M. (Zeitschrift für Gerontologie und Geriatrie, 2019)
Dysphagia is becoming increasingly more common in aging societies and, like the classical geriatric syndromes, it is a relevant functional impairment. The prevalence of dysphagia is highest in the group of old patients with neurological disorders, particularly in patients with stroke, dementia and Parkinson's disease. In the various neurological diseases of older people disease-specific factors often have a decisive influence on the clinical management of dysphagia. In addition, the concept of primary and secondary presbyphagia plays an important role in understanding age-related dysphagia. Whereas at the organ level of the International Classification of Functioning, Disability and Health (ICF) model, the diagnosis and treatment of dysphagia in neurogeriatrics have already made progress, more research is needed on the levels of activity/mobility, social environment, personal factors and the environment. This article summarizes the pathophysiological aspects as well as the current evidence for diagnosis and treatment of neurogeriatric dysphagia. Due to its high clinical relevance dysphagia should be added to the geriatric syndromes as "impaired swallowing".
Gesehen am 30.07.2019